ONLINE LEARNING DILEMMA: A CASE STUDY AT ISLAMIC BOARDING SCHOOL BABAKAN, CIWARINGIN, CIREBON - WEST JAVA - Maula, Nurkholifatul (Creative Research Journal, 2020)
The existence of this pandemic provides many changes. One of them is changes in the field of education. One of them is in the pesantren environment, which faces quite complex challenges compared to regular schools. This study aims to identify teacher perspectives and school efforts in dealing with online learning. The method used in this study used a case study approach and was analyzed using qualitative analysis. The results of this study are that the teachers at one of the junior high schools at Pondok Pesantren Babakan have the perspective that the online learning process during this pandemic period is not effective. This is due to several things. Among them: limited use of gadgets in pesantren, facilities, the lack of teachers 'ability to use IT, and students' indiscipline. Based on the perspective of the teachers above, the schools within the pesantren have various efforts to increase the effectiveness of online learning, namely: using Hybrid Learning, providing free quotas for students and teachers, and providing space for teachers to peer learning in the use of IT.Keywords: Perspective, Effort, Online Learning, and Pandemic.